Peritoneal Protein Loss Is Not Associated With Sarcopenia in Peritoneal Dialysis Patients - Do, Jun Young; Kim, A Young; Kang, Seok Hui (Frontiers in Medicine, 2021)
Introduction: Maintenance of a peritoneal membrane is essential for maintaining long-term peritoneal dialysis (PD). Peritoneal protein loss (PPL) is basically the loss of an essential nutrient, which may lead to malnutrition. We aimed to evaluate the association between PPL and sarcopenia in PD patients. Methods: We conducted a cross-sectional study from September 2017 to November 2020 on all PD patients (n = 199). Finally, the patients were divided into tertiles based on the PPL level as follows: low, middle, and high. PPL (mg/day), appendicular lean mass (ALM) using dual-energy X-ray absorptiometry, and handgrip strength (HGS) were evaluated. Sarcopenia was defined using cut-off values from the Asian Working Group for Sarcopenia. Results: The mean PPL in the low, middle, and high tertiles was 4043 ± 857, 6064 ± 558, and 9449 ± 2824 mg/day, respectively. HGS in the low, middle, and high tertiles was 23.4 ± 9.2, 23.8 ± 8.9, and 23.6 ± 8.3 kg, respectively (P = 0.967). The ALM index in the low, middle, and high tertiles was 6.0 ± 1.3, 6.0 ± 1.2, and 6.5 ± 1.1 kg/m2, respectively (P = 0..061). Multivariate analyses did not reveal significant differences in HGS and ALM index in among tertiles. The proportions of patients with sarcopenia in the low, middle, and high tertiles was 24 (36.4%), 19 (28.4%), and 21 (31.8%), respectively (P = 0.612). Conclusion: The present study showed that PPL is not independently associated with muscle mass, strength, and sarcopenia in PD patients.